Gli Studi Iberici: passato, presente, futuro - Pérez Isasi, Santiago (2021)
This article intents to offer a panoramic view of the field of Iberian Studies, a fairly young academic field devoted to the study of Iberian literatures and cultures, which has gained some level of recognition and visibility in recent years. I will present its multiple genealogy, its different origins and theoretical foundations in diverse geographical and academic spaces; its current state, with a quantitative and qualitative analysis of its publications and of its level of institutionalization, and some proposals for its future development, based on the most recent debates and criticisms about this discipline. I will try to show that, without any intention of becoming homogenic or hegemonic, Iberian Studies have promoted new ways of studying Iberian cultures superseding linguistic, political or academic barriers.